PENGARUH PENGETAHUAN WAJIB PAJAK TENTANG INFORMATION TECHNOLOGY TERHADAP INTENSITAS PENGGUNAAN INTERNET DALAM SISTEM ADMINISTRASI PERPAJAKAN TERPADU (Studi Empiris Pada Wajib Pajak Bentuk Usaha Tetap di Jakarta) - -, Amilin; Mustarikah, Anik (Jurnal Manajemen dan Keuangan, 2008)
This research is aimed to examine and find out empirical evidence of the influence of knowledge of tax payers about information technology to intensity of internet usage in integrated taxation administrate system with perception of tax payers about information technology as an intervening variable. Samples used in this research includes 42 correspondences consisting of tax payers have capital status as a Permanent Establishment (PE) in Jakarta that have losted at Kantor Pelayanan Pajak Badan dan Orang Asing Satu. Determination method sample used in this research is purposive sample (intake sample pursuant to random selected goals or purpose not). The collected of data to use primary data that is direct taken data through technique survey by using questionnaire.The quality of test in this research are validity of test to use is pearson correlation and reliability test of the research to use is cronbach alpha and then hypothesis test to use were analyzed of simple regression and multiple regression with path analysis. The results in this research are: (a) Knowledge of tax payers about information technology has significant influence to intensity of internet usage in integrated taxation administrate system. (b) Perception of tax payers about information technology has significant influence relation between knowledge of tax payers about information technology with intensity of internet usage in integrated taxation administrate system. Thus, the hypothesis indirect relation is of the research is empirically supported.Keywords: knowledge, perception, information technology, intensity of internet usage, integrated taxation administrate system.